Finite Element Analysis of Bulge Forming of Laser Welding Dimple Jacket - Peisi ZHONG; Shile MA; Yunkai YANG; Haiyan WANG; Runqiang LIU; Yuyan SUN (Medžiagotyra, 2015)
The stress-strain states of the model of laser welded dimple jacket is analyzed using ANSYS/LS-DYNA in order to determine the relation between bulging height and pressure and to achieve the controllability of pressure distension of the jacket. It is shown that in the same conditions, the bulging height increases with the increasing of the bulging pressure and the space of honeycomb. And it will decrease when the thickness of jacket plate changing larger. A table showing the relation between bulging height and pressure is obtained. An experiment using a test panel is conducted to certify the reliability of finite element analysis. It turns out that the data of finite element analysis is coincident with experimental data, which support finite element method based ANSYS/LS-DYNA can be an efficient way to research the laser welded dimple jacket. The relation table is useful as guidance for the fabrication process. DOI: http://dx.doi.org/10.5755/j01.ms.21.4.9704